2014
DOI: 10.1097/aog.0000000000000050
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Feasibility of Phone Follow-up After Early Medical Abortion in Vietnam

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 12 publications
2
54
0
Order By: Relevance
“…14,22,23 Outcomes by gestational age were reported for 12,050, 4,032, and 2,153 women with pregnancies 49 days or less, 50-56 days, and 57-63 days of gestation, respectively. All studies used 800 micrograms misoprostol buccally 11,[14][15][16][22][23][24][25][26][27][28][29][30] except for one study that reported clinical outcomes with 400 micrograms misoprostol buccally. 31 One study described the actual time interval at which patients administered misoprostol after mifepristone, reporting a median interval of 48 hours (range 25-52 hours) for women who took mifepristone at home and a median interval of 47 hours (range 26-54 hours) for women that took mifepristone in the clinic.…”
Section: Resultsmentioning
confidence: 99%
“…14,22,23 Outcomes by gestational age were reported for 12,050, 4,032, and 2,153 women with pregnancies 49 days or less, 50-56 days, and 57-63 days of gestation, respectively. All studies used 800 micrograms misoprostol buccally 11,[14][15][16][22][23][24][25][26][27][28][29][30] except for one study that reported clinical outcomes with 400 micrograms misoprostol buccally. 31 One study described the actual time interval at which patients administered misoprostol after mifepristone, reporting a median interval of 48 hours (range 25-52 hours) for women who took mifepristone at home and a median interval of 47 hours (range 26-54 hours) for women that took mifepristone in the clinic.…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted in the United States and Vietnam [12][13][14] demonstrate that the semiquantitative pregnancy test effectively detects ongoing pregnancy as early as one week after medical abortion. In a large randomized clinical trial conducted by Ngoc et al [14] in Vietnam, fewer women in the home semiquantitative pregnancy test group were lost to follow-up when compared to women in the clinic follow-up group. In all studies, women reported that the semiquantitative pregnancy test is easy to use [12][13][14].…”
Section: Introductionmentioning
confidence: 98%
“…Alternatively, telephone follow-up with a home UPT eliminates an in-person visit. Studies have evaluated regimens utilizing telephone evaluation and high-sensitivity UPT [5,6], low-sensitivity UPT [7,8], and semi-quantitative UPT [9,10], and all appear effective in detecting ongoing pregnancies. In the United States, the high-sensitivity UPT is commercially available and can be integrated into clinical practice.…”
Section: Introductionmentioning
confidence: 99%